The Role Of Forensic Autopsy In Proof Of The Crime Of Planning Murder - Liana, Nora; Rahmayanti; Ade Ira Octa Femi; Rifki Mulia; Rusli; Muhammad Hatta (International Journal of Law, Social Science, and Humanities, 2024)
Forensic autopsy plays a crucial role in proving the crime of premeditated murder. The autopsy process not only helps reveal the cause of death, but also provides physical evidence that can link the suspect to the crime. In a legal context, autopsy results are an important element in investigations and trials, providing a strong basis for the public prosecutor to prove the perpetrator's intentions and modus operandi. In Indonesia, the Health Law, especially Law Number 17 of 2023, regulates the importance of health services related to death. In this case, a forensic autopsy is regulated to ensure that the process of identification and analysis of death is carried out professionally and in accordance with medical ethics. Apart from that, this law also emphasizes collaboration between medical personnel and law enforcement officers in handling suspicious death cases. Thus, a forensic autopsy not only functions as a tool of evidence in court, but also as a form of moral and legal responsibility in handling premeditated murder cases, ensuring that every unnatural death is handled with thoroughness and integrity. Forensic autopsy has a crucial role in proving the crime of premeditated murder. This research aims to analyze the contribution of forensic autopsies in the investigation and evidence process in court. The method used is document analysis and case studies, by collecting data from autopsy reports, court decisions, and related legal documents, including the Health Law which regulates autopsy procedures and the use of the results in criminal cases. The research results show that a forensic autopsy not only identifies the cause of death, but also provides important evidence regarding the time of death, the method of murder, and the possible involvement of other parties. These findings support the importance of integrating autopsy results in the legal process, while also emphasizing the need for compliance with the Health Law which guarantees the ethical and professional implementation of autopsies. In conclusion, forensic autopsy is a vital tool in the investigation of premeditated murder cases, providing a strong scientific basis for the judicial process and law enforcement.